The epigenetic regulation between dietary bioactives and DNA methylation via multiple pathways - Shiye Lin; Wenqi Huang; Xincheng Wu; Juan Carlos Mejuto Fernández; Mohamed A. Farag; Hui Cao (Phytochemistry Reviews, 2026)

Advances in dietary bioactives: Unlocking chromatin accessibility - Wenqi Huang; Shiye Lin; Yi Yuan; Mohamed A. Farag; Hui Wang; Jianbo Xiao (Phytochemistry Reviews, 2026)

Exploring the mechanism of flavonoid amination and its potential biological implications from an in-vitro and in-vivo perspective - Pengren Zou; Celia Costas; Rui Lu; Carla Cameselle; Shiye Lin; Fan Zhang; Zhaojun Wei; Paz Otero (Critical Reviews in Food Science and Nutrition, 2026)

UPLC-ESI-MS/MS-based chemometric approach for investigating the effect of conventional versus modern extraction methods on polyphenols recovery from grape seed wastes - Shengxiong Chen; Yi Yuan; Fan Zhang; Shiye Lin; Pengren Zou; Mohamed A. Farag; Jesus Simal-Gandara; Hui Cao; Jianbo Xiao (Food Chemistry, 2025)

Unveiling grape seed extract phytochemical composition, antioxidant, and immunostimulant action mechanisms in Caenorhabditis elegans and Drosophila melanogaster - Wenqi Huang; Shiye Lin; Xincheng Wu; Haoming Wu; Shengxiong Chen; Hui Cao; Jianbo Xiao (Food Bioscience, 2025)

Exploring the mechanism of flavonoids modification by dimerization strategies and their potential to enhance biological activity - Pengren Zou; Paz Otero; Juan C. Mejuto; Jesus Simal-Gandara; Jianbo Xiao; Carla Cameselle; Shengxiong Chen; Shiye Lin; Hui Cao (Food Chemistry, 2025)

Stability and degradation mechanism of (−)-epicatechin in thermal processing - Wenqi Huang; Shiye Lin; Hui Cao (Food Chemistry, 2025)

Triclocarban and triclosan promote breast cancer progression in vitro and in vivo via activating G protein-coupled estrogen receptor signaling pathways - Ting-Ting He; Xin Li; Jie-Zhi Ma; Yuan Yang; Shiye Zhu; Jianhua Zeng; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2024)

Thermal degradation of (2R, 3R)-dihydromyricetin in neutral aqueous solution at 100 ℃ - Haolin Zhang; Shiye Lin; Ruiwei Xie; Weizhi Zhong; Hui Wang; Mohamed A. Farag; Hidayat Hussain; Randolph R.J. Arroo; Xiaojia Chen; Jianbo Xiao (Food Chemistry, 2024)

Large quantities of small microplastics permeate the surface ocean to abyssal depths in the South Atlantic Gyre - Shiye Zhao; Erik R. Zettler; Ryan P. Bos; Peigen Lin; Linda A. Amaral‐Zettler; Tracy J. Mincer (Global Change Biology, 2022)
Hundreds of studies have surveyed plastic debris in surface ocean gyre and convergence zones, however, comprehensive microplastics (MPs, ≤5 mm) assessments beneath these surface accumulation areas are lacking. Using in situ high‐volume filtration, Manta net and MultiNet sampling, combined with micro‐Fourier‐transform‐infrared imaging, we discovered a high abundance (up to 244.3 pieces per cubic meter [n m −3 ]) of small microplastics (SMPs, characteristically 300 μm) concurrently collected in MultiNet samples. Higher‐density polymers (e.g., alkyd resins and polyamide) comprised >65% of the total pump sample count, highlighting a discrepancy between polymer compositions from previous ocean surface‐based surveys, typically dominated by buoyant polymers such as polyethylene and polypropylene. Contrary to previous reports stating LMP preferentially accumulated at density gradients, SMP with presumably slower sinking rates are much less influenced by density gradients, thus resulting in a more even vertical distribution in the water column, and potentially longer residence times. Overall, our findings suggest that SMP is a critical and largely underexplored constituent of the oceanic plastic inventory. Additionally, our data support that weak current systems contribute to the formation of SMP hotspots at depth, implying a higher encounter rate for subsurface particle feeders. Our study unveils the prevalence of plastics in the entire water column, highlighting the urgency for more quantification of the deep‐ocean MP, particularly the smaller size fraction, to better understand ecosystem exposure and to predict MP fate and impacts.